2011
DOI: 10.1093/icb/icr016
|View full text |Cite
|
Sign up to set email alerts
|

The Tubercles on Humpback Whales' Flippers: Application of Bio-Inspired Technology

Abstract: The humpback whale (Megaptera novaeangliae) is exceptional among the large baleen whales in its ability to undertake aquabatic maneuvers to catch prey. Humpback whales utilize extremely mobile, wing-like flippers for banking and turning. Large rounded tubercles along the leading edge of the flipper are morphological structures that are unique in nature. The tubercles on the leading edge act as passive-flow control devices that improve performance and maneuverability of the flipper. Experimental analysis of fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
115
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(122 citation statements)
references
References 32 publications
4
115
1
2
Order By: Relevance
“…This is related to the presence of the counter-rotating streamwise vortices which tend to accelerate the fluid in between them by adding momentum, and thus confer to the fluid the extra amount of kinetic energy necessary to prevent local separation. This analysis, obtained in a massively separated flow configuration, is in good agreement with the one proposed recently in [19] to explain the delay of stall angle observed in the presence of leading edge bumps.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This is related to the presence of the counter-rotating streamwise vortices which tend to accelerate the fluid in between them by adding momentum, and thus confer to the fluid the extra amount of kinetic energy necessary to prevent local separation. This analysis, obtained in a massively separated flow configuration, is in good agreement with the one proposed recently in [19] to explain the delay of stall angle observed in the presence of leading edge bumps.…”
Section: Resultssupporting
confidence: 91%
“…In particular, the vorticity appears to roll up into a vortex tube which is initially vertical, and then immediately tilted into the streamwise direction, as it is advected by the mean stream. This Kelvin-Helmholtz-driven scenario suggests a completely different mechanism for the generation of the streamwise rollers than the "delta wing" one proposed by other authors [1,19] and is similar to conceptual models for the generation of quasi streamwise vortices from the destabilization of wall streaks in near wall turbulence [23].…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The significance of these vortices in affecting aerodynamic behaviour was also observed by Stanway (2008) in PIV measurements of the flow in the vicinity of a serrated leading edge. A number of researchers (Fish & Lauder 2006;Fish et al 2011;Zhang et al 2013;Van Nierop et al 2008) have investigated the mechanism by which stall can be delayed by the introduction of serrations at the aerofoil leading edge. They observed that the LE serrations generate streamwise vortices, which were attributed to greatly enhanced momentum transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of large sinusoidal tubercles and the high aspect ratio of flippers on humpback whales leads to an increase of the lift to drag ratio and enables it to do sharp banking turns, and to be more maneuverable compared to other species in spite of its massive body (Fish and Battle 1995;Fish et al 2011). Wind tunnel experiments conducted by Miklosovich et al (2004) showed that the tubercles cause the flipper to have a greater stall angle and maximum lift coefficient.…”
Section: Introductionmentioning
confidence: 99%